Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.26434/chemrxiv-2022-8h07c-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-native Anionic Ligand Binding and Reactivity in Engineered Variants of the Fe(II)- and α-Ketoglutarate-Dependent Oxygenase, SadA

Abstract: Mononuclear non-heme Fe(II)- and -ketoglutarate dependent oxygenases (FeDOs) catalyze site-selective C-H hydroxylation. Variants of these enzymes in which a conserved Asp/Glu residue in the Fe(II)-binding facial triad is replaced by Ala/Gly can, in some cases, bind various anionic ligands and catalyze non-native chlorination and bromination reactions. In this study, we explore the binding of different anions to a FeDO facial triad variant, SadX, and the effects of that binding on HO• vs. X• rebound. We establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Analysis of product distributions for SadX variants in the azidase lineage revealed subtle relationships between the site and chemoselectivity of the azidation, chlorination, and hydroxylation reactions catalyzed by these enzymes (Figure 2C). As previously reported, [47] SadX prefers hydroxylation to chlorination by over two-fold, and a similar preference for hydroxylation over azidation is observed. Notably, however, hydroxylation and chlorination occur at the βposition of the substrate, while azidation occurs at the 𝛾-position.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Analysis of product distributions for SadX variants in the azidase lineage revealed subtle relationships between the site and chemoselectivity of the azidation, chlorination, and hydroxylation reactions catalyzed by these enzymes (Figure 2C). As previously reported, [47] SadX prefers hydroxylation to chlorination by over two-fold, and a similar preference for hydroxylation over azidation is observed. Notably, however, hydroxylation and chlorination occur at the βposition of the substrate, while azidation occurs at the 𝛾-position.…”
Section: Resultssupporting
confidence: 86%
“…Recently, we reported that expression of this enzyme is improved by fusing it to maltose binding protein (MBP) to generate MBP-SadA D157G (hereafter SadX), and we evaluated SadX activity on N-succinyl leucine (1a) in the presence of different anions. [47] SadX exhibits relatively broad scope with respect to X • rebound (X • = Cl • , Br • , N3 • , NCO • ), suggesting that it could serve as a useful platform for non-native FeDO catalysis. The improved expression of SadX allowed for LC/MS analysis of non-native X • rebound in crude E. coli cell lysate containing the desired Xsalt and excess ascorbate [48] (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we explored the binding of different anions, X – , to an FeDO facial triad variant, SadX, and the effects of anion binding on HO • and X • rebound. Spectrophotometric titrations revealed that several anions known to bind the Fe­(II) center of other FeDHs and FeDO facial triad variants also bound to SadX, and evidence for fluoride binding not reported for other systems was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to chlorinate and brominate a variety of substrates including amino acids, nucleotides, and natural products make them a highly versatile biocatalytic platform that invite further optimization. In addition to halogenation, these enzymes have also been shown to functionalize C-H bonds with azide (Büchler et al, 2022;Chan et al, 2022;Matthews et al, 2014;Neugebauer et al, 2019) and nitrite (Matthews et al, 2014), albeit with disappointingly low yields. A variety of methods have been used to determine substrate affinity in these and related classes of enzymes, including tryptophan fluorescence (Martin et al, 2019), SPR (Hu et al, 2015), and UV-Vis spectral shift-based methods (Chan et al, 2022;Matthews et al, 2014;Price et al, 2003;Ryle et al, 1999) to name a few.…”
Section: Introductionmentioning
confidence: 99%